ANALISIS KEMUNGKINAN PENERAPAN LAPORAN BERKELANJUTAN SEBAGAI LAPORAN TAHUNAN PADA PERGURUAN TINGGI - Budi Rofelawaty; Rakhmi Ridhawati (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research seeks to explore the needs of the information required by stakeholders as management accountability college, so it can be prepared the annual reporting form that is required to describe the performance of financial and other information about the operational and development PT future. The research method used in this research is descriptive qualitative method, the process of extracting data through direct interviews structured with informants of stakeholders college, then the results of our interview in-depth analysis to collate and make adjustments to the rules Kemenristek dikti and regulations BAN PT, reporting is required for a college. The results showed annual reports uploaded or composed by several major colleges in Indonesia, there are still about reporting is dominated economic performance, in accordance with SFAS No. 45, while the operating performance reported by the academic colleges to PDPT in Kemenristek dikti, are not integrated and reflect the sustainability of the college. Researchers proposed the application of sustainable annual report which disclose the results or outcomes that occurred during a period in the context of the commitment, strategy, approach to the management of PT.